A construção da cultura capitalista na religião adventista do sétimo dia: décadas de 1980 a 2020 - Azevedo, Milton Aparecido (2022)
This research aims to be based on the theme of the emergence of the Seventh-day Adventist Church and how its teachings may have contributed to shaping in its members a capitalist culture and a competitive and individualistic vision, typically characteristic of the market economy. The emergence of Adventism in the 19th century occurred in parallel with the consolidation of the capitalist order and, consequently, this religiosity behaved much more than a mere religious society. The objective of the research is to identify and analyze the relationship of values linked to the capitalist mentality, such as individualism and economic progress, which passes through the said church and reaches its members. This work was possible through a theoretical-methodological review, having as main reference "the Protestant ethics and the spirit of capitalism" of Max Weber, and the collection of data and interviews with the subjects of adventism of the three churches existing in the city of Assis Chateaubriand/PR. The confrontation of the empirical part with the Weberian theoretical-methodological framework allowed us to identify the relationship between Adventists, or the vast majority of them, and the capitalist mentality today. Therefore, it was possible to understand the insertion of Adventists in the market economy in Assis Chateaubriand/PR, as well as that work and resilience were remarkable elements among them and that this drove them to the labor market and entrepreneurship.